PENGARUH CAPITAL INTENSITY, INVENTORY INTENSITY, PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (STUDI KASUS PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Evan Jasper (Awatara Publisher, 2023)
In the face of a 16.3% decline in revenue from the Food and Beverage Subsector (attributed to the downturn in the economic cycle), businesses find themselves presented with an opportunity to implement drastic tax measures. This entails reducing tax costs through meticulous tax planning and adjustments to tax liabilities. The research objective is to investigate the impact of capital intensity, inventory intensity, profitability, and leverage on tax aggressiveness within the manufacturing companies of the Food and Beverage Subsector listed on the Indonesia Stock Exchange during the period 2020-2022. Employing a quantitative approach and validation methods, the study reveals that capital intensity and leverage exhibit no influence on tax aggressiveness, both partially and simultaneously. Conversely, inventory intensity and profitability are found to significantly impact tax aggressiveness.